Effect of phosphatidylinositol-3 kinase inhibition on ovotoxicity caused by 4-vinylcyclohexene diepoxide and 7, 12-dimethylbenz[a]anthracene in neonatal rat ovaries - Keating, Aileen F. (2009)
4-vinylcyclohexene diepoxide (VCD) is an ovotoxicant that specifically destroys primordial and small primary follicles in the ovaries of mice and rats. In contrast, 7,12-dimethylbenz[a]anthracene (DMBA) is ovotoxic to all ovarian follicle classes. This study investigated phosphatidylinositol-3 kinase signaling involvement in VCD- and DMBA-induced ovotoxicity. Postnatal day (PND) 4 Fischer 344 (F344) rat whole ovaries were cultured for 2–12d in vehicle control, VCD (30 μM), or DMBA (1 μM), ± PI3 kinase inhibitor LY294002 (20 μM) or its inactive analog LY303511 (20 μM). Following culture, ovaries were histologically evaluated, and healthy follicles were classified and counted. PI3 kinase inhibition had no effect on primordial follicle number, but reduced (P < 0.05) small primary and larger follicles beginning on d4. VCD caused primordial and small primary follicle loss (P < 0.05) beginning on d6. With PI3 kinase inhibition, VCD did not affect primordial follicles (P > 0.05) at any time, but did cause loss (P < 0.05) of small primary follicles. DMBA exposure caused primordial and small primary follicle loss (P < 0.05) on d6. Further, DMBA-induced primordial and small primary follicle loss was greater with PI3 kinase inhibition (P < 0.05) than with DMBA alone. These results support that 1) PI3 kinase mediates primordial to small primary follicle recruitment, 2) VCD, but not DMBA, enhances ovotoxicity by increasing primordial to small primary follicle recruitment, and 3) in addition to xenobiotic-induced ovotoxicity, VCD is also a useful model chemical with which to elucidate signaling mechanisms involved in primordial follicle recruitment.